Saving Stabilizing Structure Treatment With Bilateral-Contralateral Decompression for Spinal Stenosis in Degenerative Spondylolisthesis Using Unilateral Biportal Endoscopy - Dong Hyun Lee; Dong-Geun Lee; Choon Keun Park; Jae-Won Jang; Jin Sub Hwang; Jun Yong Kim; Yong-Eun Cho; Sang Won Lee; Dong Chan Lee; Bang Sang Han; Sang Yeop Han (Neurospine, 2023)
Objective This study aimed to evaluate the treatment of spinal stenosis with spondylolisthesis using bilateral-contralateral unilateral biportal endoscopic (UBE) decompression to minimize facet joint damage. Methods We retrospectively evaluated 42 patients with grade 1 spondylolisthesis who underwent bilateral-contralateral UBE decompression between July 2018 and September 2019. To identify segmental instability, static and dynamic images from preoperative and postoperative procedures and final follow-up radiographs were reviewed. Lateral radiograph slippage ratio, sagittal motion, and facet joint preservation were evaluated. Clinical assessments were conducted using the visual analogue scale (VAS), Oswestry Disability Index (ODI), and modified MacNab criteria. Results The average final follow-up period was 26.5 ± 1.3 months. The average preoperative slip percentage was 15.70% ± 5.25%, which worsened to 18.80% ± 5.41% at the final follow-up (p < 0.005). The facet joint preservation rate was 95.6% ± 4.1% on the contralateral side. Improvements in the VAS scores (leg pain: from 7.9 ± 2.2 to 3.1 ± 0.7; p < 0.005; back pain: from 7.2 ± 3.0 to 2.8 ± 1.0; p < 0.005) were observed at the final follow-up. The mean preoperative ODI was 26.19 ± 3.42, which improved to 9.6 ± 1.0 (p < 0.005). Thirteen patients exhibited delayed focal segmental instability following decompression. Despite the absence of symptoms or improvement with conservative treatment in the majority of patients with delayed instability, two patients required fusion surgery to address the instability. Additionally, 2 patients developed facet synovial cysts, while 2 experienced spinous process fractures. Conclusion Bilateral decompression with a contralateral UBE approach could be an effective and alternative treatment method to reduce instability in spinal stenosis with grade 1 spondylolisthesis.